Analisis Kualitas Produk Scooter Matic Ditinjau Dari Sisi Konsumen Muslimah - Lola Malihah (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2022)
This research aims to analyze the quality of scooter matic products of various types and brands from the muslimah consumer side. This twisting is a field sharpener with a descriptive quantitative approach. In this study, a survey of 150 Muslim women consumers was conducted. The results of this study show that the dominant motor vehicle brands used are Honda Scoopy, Honda Beat, and Honda Vario. As many as 82% of santriwati and students in Yayasan Darussalam Martapura who are required to wear clothes in accordance with sharia principles in the form of long and wide robes or long-handed shirts combined with wide long skirts claim to have experienced long clothes or dresses worn. when driving damaged because it was scorched by the exhaust. This is due to the exhaust of scooter matic vehicles that are open so that they can easily burn clothes while driving. Therefore, it is expected that there will be attention and consideration of this complaint in order to make the latest breakthrough in the development of scooter matic products.